2011
DOI: 10.1021/ma201015y
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptoids from N-Substituted Glycine N-Carboxyanhydrides: Hydrophilic, Hydrophobic, and Amphiphilic Polymers with Poisson Distribution

Abstract: Preparation of defined and functional polymers has been one of the hottest topics in polymer science and drug delivery in the recent decade. Also, research on (bio)degradable polymers gains more and more interest, in particular at the interface of these two disciplines. However, in the majority of cases, combination of definition, functionality and degradability, is problematic. Here we present the preparation and characterization (MALDI–ToF MS, NMR, GPC) of nonionic hydrophilic, hydrophobic, and amphiphilic N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
237
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(251 citation statements)
references
References 68 publications
9
237
0
1
Order By: Relevance
“…The living character of the nucleophilic ring-opening polymerization (NuLROP) of NNCAs other than Sar-NCA was shown by Luxenhofer and co-workers [22]. In particular, the successful preparation of a pentablock quinquiespolymer highlighted the unique character of the NNCA NuLROP [23].…”
Section: Open Accessmentioning
confidence: 99%
“…The living character of the nucleophilic ring-opening polymerization (NuLROP) of NNCAs other than Sar-NCA was shown by Luxenhofer and co-workers [22]. In particular, the successful preparation of a pentablock quinquiespolymer highlighted the unique character of the NNCA NuLROP [23].…”
Section: Open Accessmentioning
confidence: 99%
“…[15][16][17][18][19][20] The relative cell viability was found to be dependent on the polymer composition and concentration. It was found that relative cell viability decreases with increasing polymer concentration for all polymers (Figure 13).…”
Section: Cytotoxicitymentioning
confidence: 97%
“…In recent years, the substrate scope for polymerization studies was further expanded to include a variety of R-NCA monomers bearing various N-substituents ( Figure 2). [5,6,[15][16][17][18][19][20][21][22] Luxenhofer et al demonstrated that the polymerizations of Me-NCAs using benzyl amine initiators were shown to proceed in a controlled manner without chain transfer or termination events, producing polysarcosines with narrow Poisson distribution (PDI < 1.1-1.3) and M n s that can be controlled by the initial monomer to initiator feed ratios. [56] The molecular distribution remains narrow (PDI 5 1.01-1.07) even after ten sequential polymerizations of Me-NCA monomers (DP < 100), attesting to the robustness of the living polymerization and suggesting the potential uses of the methods towards the synthesis of well-defined block copolypeptoids via sequential monomer addition.…”
Section: Synthesis Of Linear Polypeptoidsmentioning
confidence: 99%
See 2 more Smart Citations